The main directions of the solution of the problems of providing the houses at affordable prices in the azerbaijan republic by effective project management of housing construction projects (Economics and region, 2019)
It is very important to provide of housing to the population at affordable prices in the developing countries. It should be noted that the concept of “reasonable price” is differently stated in the experience of different countries of the world. The studies show that today about 330 million families in developing and also in developed countries are faced with the problem of obtaining quality housing at affordable prices, and this figure is gradually increasing. Despite the fact that the number of apartments built in the Azerbaijan Republic, which is rapidly developing in the residential real estate market, is quite large, it is impossible to purchase housing for the low-income population, since the prices are very high. It also plays a role the high price of land in cities and low mortgage lending. In housing construction investments the proportion invested in land purchases is very high. Taking into account the above, the Strategic Road Map was developed and adopted to increase the affordability of housing in the Republic of Azerbaijan. To achieve the nominated goals established the State Agency for Housing Construction (abbreviation in Azeri-MIDA) and started construction of two large residential complexes. This article touches upon the task of providing the population of Azerbaijan with housing at affordable prices.
Keywords: construction; affordable housing; project management; the plot of land; mortgage lending; population income; cost of housing; residential complexes